Penyuluhan Hukum tentang Tindak Pidana Pemalsuan Dokumen kepada Masyarakat Desa Bantarpanjang Berdasarkan Pasal 263 KUHP - Tedy Subrata; Suandi Suandi; Markuat Markuat; Salmah Salmah; Turija Turija; Chairul Aman (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
This community service activity was conducted in Bantarpanjang Village, Tigaraksa District, Tangerang Regency, with the theme "Criminal Violations Against Document Forgery According to Article 263 of the Indonesian Criminal Code". As a state governed by law, Indonesia mandates that all actions of its citizens must be based on legal principles. The rule of law must be upheld consistently to ensure justice in society. One prevalent issue today is the crime of document forgery, which is increasingly sophisticated due to technological developments. Article 263 of the Indonesian Criminal Code (KUHP) regulates two types of document forgery. Paragraph (1) addresses individuals who create or alter documents to generate rights or obligations, or to be used as valid evidence with deceptive intent. Paragraph (2) covers those who deliberately use such forged documents as if they were genuine, which may result in harm to others. Legal sanctions for violating this article include imprisonment for up to six years and/or a fine of up to one billion rupiah. Through this community legal education, the public is expected to gain a better understanding of the legal consequences of document forgery and to increase awareness of the importance of maintaining integrity and legal compliance in their daily lives.